2020
DOI: 10.21203/rs.3.rs-69357/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ELOVL2: a novel tumor suppressor attenuating tamoxifen resistance in breast cancer

Abstract: Background To comprehensively understand the molecular mechanism of tamoxifen resistance (TamR) acquisition by epigenetically regulated genes, it is essential to identify pivotal genes by genome-wide methylation analysis and verify their function in xenograft animal model and cancer patients. Methods The MCF-7/TamR breast cancer cell line was developed and a genome-wide methylation array was performed. The methylation and expression of ELOVL2 was validated in cultured cells, xenografted tumor tissue, and bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…In our previous study, genome-wide methylation was analyzed in MCF-7/tamR cells to identify epigenetically regulated genes responsible for drug resistance [ 29 ]. In the current study, we focused on hypomethylated genes, as numerous oncogenes have been reported to be upregulated by hypomethylation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, genome-wide methylation was analyzed in MCF-7/tamR cells to identify epigenetically regulated genes responsible for drug resistance [ 29 ]. In the current study, we focused on hypomethylated genes, as numerous oncogenes have been reported to be upregulated by hypomethylation.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned in vitro observations were tested in vivo by evaluating whether MMP1 can drive tumor cell growth and drug resistance in a xenograft mouse model. First, MMP1 expression was examined in the tumor tissues obtained after xenografting MCF-7 and MCF-7/tamR cells into nude mice, as described in our previous study [ 29 ]. In situ immunohistochemistry of tumor sections validated the elevated MMP1 expression in MCF-7/tamR cells compared to that in parental MCF-7 cells ( Figure 4 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors examined the relationship between ELOVL2 expression and metastatic relapse-free in a BC cohort with a follow-up of ten years, resulting in the discovery of an association between lower ELOVL2 expression levels and shorter metastasis-free survival and higher tumor grade [116]. A recent study investigating the molecular mechanisms of tamoxifen resistance in BC confirmed these findings and described lower ELOVL2 expression in tamoxifenresistant models and ELOVL2 downregulation in patients with tamoxifen resistance [135].…”
Section: Multi-omics Studies Of Bc Prognosismentioning
confidence: 99%